Pengaruh Perawatan Tali Pusat Dengan Menggunakan Air Hangat Terhadap Waktu Lepasnya Tali Pusat Pada Neonatus - Yunita Amilia (Universitas Nazhatut Thullab Al- Muafa Sampang, 2021)
Introduction: Umbilical Cord care is an act of treatment and the binding cord that causes physical separation mothers with babies. Cord care was performed using a cotton swab dipped in warm water and then dried with a clean gauze. Cord care is good and true positive impact that the cord will take on day-5 to day-7. Methods: This research is a type of pre-experimental design with One Shot Case-Study. The entire population of neonates in BPS with a sample of 12 neonates using Consecutive Sampling techniques. Data obtained from the observation after several days of treatment without a comparison group. To know the significant value and the effect of treatment, and then the data were analyzed using the Kolmogorov-Smirnov test with significance α = 0.05. Result: The results were obtained rapidly loose cord as much as 1 neonates, 10 neonates and slow normal one neonates were then tested with the Kolmogorov-Smirnov Test got value P = 0.031, so that H1 is accepted that there is the influence of cord care using warm water with respect to time the release of the cord in neonates. Conclusions: Based on the results of research conducted, about the care of the umbilical cord with warm water has an influence on the release time of the umbilical cord. Thus the health workers are encouraged to use warm water treatment techniques in treating neonatal umbilical cord.